[Obas de Tadao Ando] (GA : Architect)
Se compilan obras de Tadao Ando. Contiene: Soseikan (Yamaguchi House), Takarazuka, Hyogo, 1974-1975, 1981-1982 (addition). Twin Wall, 1975. Tezukayama Tower Plaza, Sumiyoshi, Osaka, 1975-1976. Tezukayama House, (Manabe House), Abeno, Osaka, 1976-1977. Wall House (Matsumoto House), Ashiya, Hyogo, 1976-1977. Okamoto Housing Project, Kobe, Hyogo, 1976. Art Gallery Complex Project, Minato, Tokyo, 1977. Step, Takamatsu, Kagawa, 1977-1980. Okusu House, Setagaya, Tokyo, 1977-1978. Glass Block House (Ishihara House), Ikuno, Osaka, 1977-1978. Glass block Wall (Horiuchi House), Sumiyoshi, Osaka, 1977-1979. Rokko Housing I, Kobe, Hyogo, 1978-1983. Kashino House, Ashiya, Hyogo, 1979-1981, 1983-1984 (addition). Ishii House, Hamamatsu, Shizuoka, 1980-1982. Festival, Naha, Okinawa, 1980-1984. BIGI Atelier, Shibuya, Tokyo, 1980-1983. Nakanoshima Project, Kita, Osaka, 1980. Fukuhara Clinic, Setagaya, Tokyo, 1981-1986. Townhouse in Kujo (Itzutsu House), Nishi, Osaka, 1981-1982. Kaneko House, Shibuya, Tokyo, 1982-1983. Iwasa House, Ashiya, Hyogo, 1982-1984. Kidosaki House, Setagaya, Tokyo, 1982-1986. TIME’S, Nakagyo, Kyoto, 1983-1984. TIME’S II, Nakagyo, Kyoto, 1986. Atelier Yoshie Inaba, Shibuya, Tokyo, 1983-1985. JUN Port Island Building, Kobe, Hyogo, 1983-1985. Mon-petit-chou, Sakyo, Kyoto, 1983-1985. Hata House, Nishinomiya, Hyogo, 1983-1984. Sasaki House, Minato, Tokyo, 1984-1986. Nakayama House, Suzaku, Nara, 1983-1985. Guest House for Hattori House, Abeno, Osaka, 1984-1985. Taiyo Cement Headquarters Building, Fukushima, Osaka, 1984-1986. TS Building, Kita, Osaka, 1984-1986. Old / New Rokko, Kobe, Hyogo, 1985-1986. Chapel on Mt. Rokko, Kobe, Hyogo, 1985-1986. Tea House in Oyodo, Oyodo, Osaka, 1985. Main Pavilion for the Tennoji Fair, Tennoji, Osaka, 1986-1987. Karaza Theater, 1985-1987. Rokko Housing II, Kobe, Hyogo, 1985- . Shibuya Project, Shibuya, Tokyo, 1985-1987. RAIKA Headquarters Building Suminoe, Osaka, 1986- . Church on the Water, Tomamu, Hokkaido, 1985- .